A gente não é uma doença, tem muita coisa por trás! : narrativas de um grupo de pessoas portadoras de doenças crônicas sobre seu adoecimento - Manso, Maria Elisa Gonzalez (2015)
This research aims to understand the explanatory model and the therapeutic itinerary of a group of patients affected by chronic diseases who are assisted by disease management programs carried out by operators of health plans and identify strategies of self-care that relate with the explanatory model. The thesis that moves this study is that the route that the patient uses for its treatment has deep roots in his own culture, being much larger than the model used by health professionals, also generated by the culture, but restricted by the biomedical vision. The meanings of terms such as health, cure, treatment, disability, dependence and others are not always equal in both models. If the meaning is too different, adherence to the treatment will be impaired, but the patient may still have obtained relief from their suffering. The methodology applied is qualitative, gathered through interviews with people with confirmed previous medical diagnosis of chronic disease who were already undergoing treatment, accompanied by chronic diseases management programs, which, according to the hegemonic healthy model, should know the diseases that affect them with a sufficient degree of information that would allow their full compliance. Because these are people linked to health plans, with a higher socioeconomic strata, they would fit the criteria of information, income, education and access to health care that would turn them into ideal patients and adherent to therapy. Reasons for non-adherence to treatment among these participants are what motivated this research and generated the hypothesis that the therapeutic itinerary of these patients, generated and engraved in their culture, originates from an explanatory model of the illness process much wider than the hegemonic model. So these diseased would present strategies of self-care, as part of this layman model, which allows them to carry on and manage their treatment both within and without the current prevailing model, strategies those that can be seen by health professionals as noncompliance. We believe that this study achieved its objectives, supporting the initial hypothesis of the research, showing that even in a theoretically disciplined group within criteria taken as ideal for joining the biomedical model of illness and treatment, people are immersed in their culture and find loopholes for the exercise of self-care. The work also showed that the crisis of the biomedical model, in this case, stems from the microphysics power relations and from the structural conditions of the health system and the people in the group are able to identify some of these flaws. We hope this research will contribute to this relevant nowadays debate as well as collaborate in the reflections on medicine and health education, broadening the discussion to incorporate the experiences and narratives of this group of patients